2005
DOI: 10.1007/s00103-005-1166-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporoseprävalenz und assoziierte Versorgungsmuster bei Frauen im Alter ab 45 Jahren in Deutschland

Abstract: The prevalence of osteoporosis and associated factors were assessed among women 45 years and older as part of the first nationwide German Telephone Health Survey (GSTel03). A total of 14.2% of women reported that a doctor had ever diagnosed them with osteoporosis. Among these about, 15% also reported a physician-diagnosed fragility fracture, the fracture question was restricted to the subgroup of women with osteoporosis. Point estimates of overall osteoporosis prevalence increased significantly across 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
2
6
0
1
Order By: Relevance
“…Bevölkerungsrepräsentative Daten zur gegenwärtigen Verbreitung von MSKE in Deutschland sind größtenteils krankheitsspezifisch und stützen sich meist auf kleinräumige Datenerhebungen oder Diagnose-und andere Routinedaten [7,8,9,10,11,12,13,14,15,16,17]. Zu den MSKE zählen sowohl degenerative Gelenkerkrankungen (z.…”
Section: Hintergrund Und Fragestellungunclassified
“…Bevölkerungsrepräsentative Daten zur gegenwärtigen Verbreitung von MSKE in Deutschland sind größtenteils krankheitsspezifisch und stützen sich meist auf kleinräumige Datenerhebungen oder Diagnose-und andere Routinedaten [7,8,9,10,11,12,13,14,15,16,17]. Zu den MSKE zählen sowohl degenerative Gelenkerkrankungen (z.…”
Section: Hintergrund Und Fragestellungunclassified
“…Of these just short of 22% were treated with osteoporosis medication [7]. themenschwerpunkt In a German telephone survey the prevalence of osteoporosis amongst women over 45 years was determined to be 14.2%, of these 15.0% reported having suffered osteoporotic fractures [8].…”
Section: Epidemiologymentioning
confidence: 99%
“…Age-related diseases, such as osteoporosis, will therefore gain in importance (2). Because of the enormous relevance of osteoporosis for the individual and the substantial costs to the healthcare system (2), epidemiological osteoporosis research is of essential importance (2)(3)(4)(5). To date, however, only few studies have reported data on the prevalence and risk factors for osteoporosis in Germany (3)(4)(5).…”
mentioning
confidence: 99%
“…Because of the enormous relevance of osteoporosis for the individual and the substantial costs to the healthcare system (2), epidemiological osteoporosis research is of essential importance (2)(3)(4)(5). To date, however, only few studies have reported data on the prevalence and risk factors for osteoporosis in Germany (3)(4)(5). At the same time, such investigations (3)(4)(5) are often limited in terms of the selection of study subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation